Leader-follower fixed-time consensus for multi-agent systems with unknown non-linear inherent dynamics - Defoort, Michael; Polyakov, Andrey; Demesure, Guillaume; Djemai, Mohamed; Veluvolu, Kalyana (IET control theory & applications, 2015)
This study focuses on the design of fixed-time consensus for first-order multi-agent systems with unknown inherent non-linear dynamics. A distributed control protocol, based on local information, is proposed to ensure the convergence of the tracking errors in finite time. Some conditions are derived to select the controller gains in order to obtain a prescribed convergence time regardless of the initial conditions. Simulations are performed to validate the theoretical results.